Adult Spinal Hamartoma Involving Conus Medullaris: Brief Review About Associated Congenital Abnormalities and Surgical Outcome - Nazmin Ahmed (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Spinal hamartoma is an extremely rare lesion for symptomatic spinal cord compression in adult population. Without any association of spinal dysraphism and neurofibromatosis, only 3 cases have been reported in the literature. Case description: A 40-year-old man presented with lumbago femorica for 6 months. Gradually the symptoms worsened and he developed features of Cauda equina syndrome. Magnetic Resonence Imagimg demonstrated a heterogeneously hyperintense intradural extramedullary mass in both T1 and T2WI, involving conus medullaris and cauda equina, opposite to L1. Patient underwent near total resection of lesion through posterior midline approach. Histopathological features were consistent with hamartoma. Patient neurologically improved and follow up MRI at 6 months showed static small nodular tumor residue. Conclusion: To the best of our knowledge, current report is the fourth case of spinal hamartoma in adult male, without any association of spinal dysraphism and neurofibromatosis .This may be the first reported case from Bangladesh.